Prognostic value of serum Uric Acid in-hospital Mortality and Morbidity in Patients with acute Myocardial Infarction - Hossain, Md Deldar; Ferdousi, Sheuly; Islam, Md Saiful; Paul, Debatosh; Sultana, Ttuhin; Hoque, Harisul; Rahman, Md Quddusur; Banerjee, Sajal Krishna; Ahmed, Annashimuddin (University Heart Journal, 2017)
Coronary artery disease (CAD) is one of the leading causes of death in the world and also in Bangladesh. This study was carried out to evaluate that Serum uric acid is a prognostic tool in acute myocardial infarction. In this study, 108 AMI cases were enrolled. All the patients were treated and managed identically by conventional standard management protocol. During hospital stay, patients were assessed for any kind of clinical outcomes e.g good recovery, mortality and morbidity (acute LVF, cardiogenic shock, arrhythmia and heart block). Patients with higher serum uric acid (SUA>6.5mg%, Group-II) were compared with Patients with lower serum uric acid (SUA<6.5mg%, Group-I). In Group I (n=66), good recovery, morbidity and mortality were found in 43 (65.2%), 21 (31.8%), 2(3.0%) patients and in Group II (n=42), good recovery, morbidity, mortality were 13 (31%), 23 (54.8%) and 6 (14.3%) patients respectively. In group II patients having high Serum uric acid concentration had low good recovery but high morbidity and mortality compared to group I patients. In group I (n=66), good outcome and bad outcome was found in 43(65.2%), and 23 (34.8%) patients and in group II (n=42), those were in 13 (31%) and 29 (69%) patents. Logistic regression analysis of serum uric acid concentration of study subjects were done considering uric acid as independent variable but outcome as dependent variable. It was shown that the odds ratio of mortality was 5.38(95% CI p<0.007), odds ratio of morbidity was 4.10(95% CI p<0.001) and odds ratio of bad outcome was 4.67(95% CI p<0.001). This findings indicates a patient having high uric acid had 5.38 times increased mortality, 4.10 times increased morbidity and 4.67 times increased bad outcome than patients having low serum uric acid concentration. University Heart Journal Vol. 12, No. 1, January 2016; 8-11